2022
DOI: 10.1021/acssensors.2c01423
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Assisted Multifunctional Environmental Sensing Based on a Piezoelectric Cantilever

Abstract: Multifunctional environmental sensing is crucial for various applications in agriculture, pollution monitoring, and disease diagnosis. However, most of these sensing systems consist of multiple sensors, leading to significantly increased dimensions, energy consumption, and structural complexity. They also often suffer from signal interferences among multiple sensing elements. Herein, we report a multifunctional environmental sensor based on one single sensing element. A MoS 2 film was deposited on the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Apart from these, we have also shown that our fabricated flexible, all-organic device is also air-permeable for wearable electronics applications, by performing the air permeability test with water vapor from our lab-made setup. In our test, we have obtained a water vapor transmission rate (WVTR) of ∼250 g m –2 day –1 , which indicates better air permeability, breathability, and appropriateness for wearable devices and sensor applications.…”
Section: Resultsmentioning
confidence: 81%
“…Apart from these, we have also shown that our fabricated flexible, all-organic device is also air-permeable for wearable electronics applications, by performing the air permeability test with water vapor from our lab-made setup. In our test, we have obtained a water vapor transmission rate (WVTR) of ∼250 g m –2 day –1 , which indicates better air permeability, breathability, and appropriateness for wearable devices and sensor applications.…”
Section: Resultsmentioning
confidence: 81%
“…Li et al demonstrated a multifunctional environmental sensor using a single sensor composed of a MoS 2 film deposited on a piezoelectric microcantilever (Figure 29e). 1056 The MoS 2 film served as both a sensing layer and top electrode, and the humidity and CO 2 concentration sensing was demonstrated using a single sensor. The sensor demonstrated excellent performance in detecting humidity, with high resolution (0.3% RH), low hysteresis (5.6%), and fast response (1 s) and recovery (2.8 s) times.…”
Section: Examples Of Fully Integrated Bioelectronic Sensor Systemsmentioning
confidence: 99%
“…Multifunctional environmental sensing is of great importance for various applications, such as agriculture, pollution monitoring, and disease diagnosis. Li et al demonstrated a multifunctional environmental sensor using a single sensor composed of a MoS 2 film deposited on a piezoelectric microcantilever (Figure e) . The MoS 2 film served as both a sensing layer and top electrode, and the humidity and CO 2 concentration sensing was demonstrated using a single sensor.…”
Section: Applications For Flexible Electronicsmentioning
confidence: 99%
“…The technological progress of ML is now manifested in nearly all branches of science and technology [1–11] . Through proper handling of powerful computation and high‐throughput experimentation, ML has expedited the scientific research and technological development [12–31] . Even though the adoption of data‐guided growth of materials is inspiring to recognize the accurate potential of ML models, they should also have the potentiality over solely predictive ability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Through proper handling of powerful computation and highthroughput experimentation, ML has expedited the scientific research and technological development. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Even though the adoption of data-guided growth of materials is inspiring to recognize the accurate potential of ML models, they should also have the potentiality over solely predictive ability. The prediction and inner execution of models must offer appropriate explanation to the human specialists.…”
Section: Introductionmentioning
confidence: 99%